As propostas educacionais de higienização veiculadas pela Revista Escolar (1925-1927) - Silva, Rodrigo Pereira Dos Anjos Da [UNIFESP] (2020)
Educational journals, published in the first decades of the 20th century, were the scene of disputes and clashes between different groups that not only sought space to convey their ideas, but also wanted to impose their representations on the educational field of the time. It is within this area that this study finds its concerns. Published between January 1925 and September 1927, part of this research, Revista Escolar was a spotlight for the defense of the modern school in São Paulo and the defense of a hygienist thought. In this way, commanded by the Public Instruction Board, under the leadership of Pedro Voss, between 1925 and 1927, this Board published the Revista Escolar, receiving harsh criticism from the group that was located around the 1926 Survey, formulated by Fernando de Azevedo. In this struggle of representations for the institutionalization of a São Paulo educational model, several strategies were used by the editorial board of Revista Escolar as a way to attract the largest number of teachers from São Paulo and build an ideal reader for a peculiar reading model. However, the journal also circulated the discourse on the imperative need for the articulation of hygiene in school education. This discourse constituted a link between intellectuals in favor of the model of reading the periodicals and its critics. In other words: if there were criticisms of the teaching method and the way these methods were printed in the journal, there were no dissensions in relation to hygienic discourse. Anyway, we started from the idea that there were differences between these groups of intellectuals in the field of education, these differences need to be located and explained. In this perspective, to unravel the bellicose field of education, we analyzed the magazine in its material and didactic form, as well as the public in this way projected - the recently graduated teachers-; we also analyzed the magazine as a space for defending ideas about literacy and its forms of dissemination and the ideas for articulation between school and hygiene. Because, in the front that was formed between these different groups, in the 1920s, increasing, decreasing, excluding and including information in the journal's body, becomes morEducational journals, published in the first decades of the 20th century, were the scene of disputes and clashes between different groups that not only sought space to convey their ideas, but also wanted to impose their representations on the educational field of the time. It is within this area that this study finds its concerns. Published between January 1925 and September 1927, part of this research, Revista Escolar was a spotlight for the defense of the modern school in São Paulo and the defense of a hygienist thought. In this way, commanded by the Public Instruction Board, under the leadership of Pedro Voss, between 1925 and 1927, this Board published the Revista Escolar, receiving harsh criticism from the group that was located around the 1926 Survey, formulated by Fernando de Azevedo. In this struggle of representations for the institutionalization of a São Paulo educational model, several strategies were used by the editorial board of Revista Escolar as a way to attract the largest number of teachers from São Paulo and build an ideal reader for a peculiar reading model. However, the journal also circulated the discourse on the imperative need for the articulation of hygiene in school education. This discourse constituted a link between intellectuals in favor of the model of reading the periodicals and its critics. In other words: if there were criticisms of the teaching method and the way these methods were printed in the journal, there were no dissensions in relation to hygienic discourse. Anyway, we started from the idea that there were differences between these groups of intellectuals in the field of education, these differences need to be located and explained. In this perspective, to unravel the bellicose field of education, we analyzed the magazine in its material and didactic form, as well as the public in this way projected - the recently graduated teachers-; we also analyzed the magazine as a space for defending ideas about literacy and its forms of dissemination and the ideas for articulation between school and hygiene. Because, in the front that was formed between these different groups, in the 1920s, increasing, decreasing, excluding and including information in the journal's body, becomes more than an artifice of the publishing process, they are tools that help to shape a certain thought, thus seeking to dominate and dominate certain representations. To analyze this field of disputes, in this dissertation, hygiene and the project (s) for its implementation in São Paulo schools proposed by Revista Escolar are the central issue.e than an artifice of the publishing process, they are tools that help to shape a certain thought, thus seeking to dominate and dominate certain representations. To analyze this field of disputes, in this dissertation, hygiene and the project (s) for its implementation in São Paulo schools proposed by Revista Escolar are the central issue.